An exploratory analysis of governance dynamics, institutional reforms and development: a comparative study of India and Bangladesh. Issue 1 (2nd January 2018) - Sarker, Abu Elias; Khalid, Saba
ABSTRACT: Governance has become a prominent issue over the last three decades or so in the intellectual and practical domains of public administration. Significant debates have proliferated about the significance, domains and types of governance and their implications for democracy and development, particularly in developing countries. Amidst the debates on the relationship between governance and development, political settlements analysis has become quite prominent that focuses on the implications of political settlement for reforming and enforcing institutions leading towards negative/positive economic development. This article aims to examine how the interlocked relationships among the members of the dominant power coalition in the governing system help reform the institutions, distribute privileges, maintain stability and affect economic development with particular reference to India and Bangladesh.